GENETIC DIVERSITY, AGRONOMICAL CHARACTERISTICS AND RESISTANCE TO BLUE DISEASE IN SOME LOCAL AND INTRODUCED COTTON CULTUVARS - Nguyệt, Nguyễn Thị Minh (Vietnam Journal of Biotechnology, 2011)
The genetic diversity among 49 local and infroduced cotton cultivars belonging to Gossypium hirsutum L., Gossypium barbadense L. and Gossypium arboretum L. were investigated using 50 SSR markers, which provided 128 alleles. The genetic relationships among 49 cotton genot)^es were examined using SM coefficient to compute the similarity matrices. UPGMA analysis was performed and dendrogram was constructed. The genetic similarity ranged from 0.48 to 0.97 with an average of 0.8 indicated sufficient genetic diversity does exist within the cotton collection. Dendrogram clustered the 49 cotton genotypes into three distinct groups: one of 21 G. hirsutum L. genotypes, one of 16 G. barbadense L. genotypes, and the other of 12 G. arboretum L. genetypes, that are agreement with the traditional taxonomic arrangement of these cultivars. Genetic similarities among each group ranged from 0.86 to 0.96. More genetic diversity was observed in Gossypium hirsutum L. than Gossypium barbadense L. and Gossypium arboretum L.. Morphological and agronomical characteristics were also evaluated under field condition in 2007 indicated that Gossypium hirsutum L. cultivars yielded higher, but produced lower fiber quality, while Gossypium barbadense L. cultivars have lower yield but higher fiber quality. The screening of cotton blue disease under glass house condition indicated that 100% cultivars oi Gossypium hirsutum L. and Gossypium barbadense L. groups were susceptible to blue disease. In Gossypium arboretum L. group, there was only Co Nghe An variety and four elite lines developed from Co Nghe An showed resistance to blue disease. These results could be handy in parental selection tool for mapping and breeding for cotton blue disease resistance